Formulation of Effervescent Powder Using Dates Containing Myo-Inositol as Active Ingredients - aznan, nur naufal; MOHAMAD FUZI, PROF. MADYA. DR. SITI FATIMAH ZAHARAH (Enhanced Knowledge in Sciences and Technology, 2024)
The purpose of this study is to investigate at potential health advantages of myo-inositol (MI) and natural date sweetness combined in an effervescent powder medium. The first step in the research is to use the HPLC method to determined the myo-inositol compound in dates. The effervescent powder’s physicochemical properties are determined in parallel. Using a mixture design software, the effervescent powder’s formulation is generated, with sodium bicarbonate and citric acid serving as the effervescent agents and myo-inositol and dates serving as variable ingredients. According to the findings, the effervescent powder’s pH is between 4.05 to 5.02. In addition, the effervescent powder dissolves in a short amount of time—between 103 and 135 seconds. Testing for water solubility shows results between 1:24 and 2:26 minutes, with little difference between the different formulations. In particular, formulation 1, which contains myo-inositol and the effervescent agent, has the highest percentage of inhibition in the DPPH testing. For the rest of the formulation which consist of a mixture of dates, myo-inositol and effervescent agent, resulted constant stage of percentage inhibition for DPPH assay in the range of 39.72 ±2.08% until 42.72 ±6.72%. This study reveals the fascinating potential of utilising dates and myo-inositol together in an effervescent powder, providing a new way of utilising each ingredient’s benefits for sweetness and health.